Peces De La Cuenca Del Río Magdalena, Colombia: Diversidad, Conservación Y Uso Sostenible 2021
DOI: 10.21068/b2020rrhhxix04
|View full text |Cite
|
Sign up to set email alerts
|

Ecología e historias de vida de los peces en la cuenca del río Magdalena, Colombia

Abstract: La elevación en los Andes es un factor definitivo en la estructura de los ensamblajes de peces y los ecosistemas en que habitan. Los ensamblajes en el río Magdalena se estructuran mediante la interacción entre el tipo de ecosistema, la elevación y el ciclo de lluvias. En este capítulo se analiza la información ecológica disponible en diferentes fuentes sobre los peces del río Magdalena y se presentan algunas características de los ensamblajes de peces. La mayor riqueza de especies se encuentra en las zonas baj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In the Magdalena-Cauca basin, these spawning sites are found in the main course and/or tributaries in portions of the channel with gentle slopes and near floodplains [ 19 ]. The presence of potamodromous species in early stages within tributaries, such as Porce River and Mata River, and in the main channel of the Nechí River, confirms that this subbasin remains an important spawning site, which had been suggested by a study on the high-water seasons of 2013–2014, where the Cesar, San Jorge, Magdalena (the portion near Barrancabermeja and Honda), Nechí, Sogamoso, Carare, and Opón Rivers are mentioned as the most important spawning areas for these species [ 12 , 19 , 22 ]. Another study reported that the spawning sites of the Cauca River are in the area between Puerto Valdivia and Mantequera (Pinillos), as well as in its tributaries (Tarazá and Nechí Rivers) [ 56 ].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In the Magdalena-Cauca basin, these spawning sites are found in the main course and/or tributaries in portions of the channel with gentle slopes and near floodplains [ 19 ]. The presence of potamodromous species in early stages within tributaries, such as Porce River and Mata River, and in the main channel of the Nechí River, confirms that this subbasin remains an important spawning site, which had been suggested by a study on the high-water seasons of 2013–2014, where the Cesar, San Jorge, Magdalena (the portion near Barrancabermeja and Honda), Nechí, Sogamoso, Carare, and Opón Rivers are mentioned as the most important spawning areas for these species [ 12 , 19 , 22 ]. Another study reported that the spawning sites of the Cauca River are in the area between Puerto Valdivia and Mantequera (Pinillos), as well as in its tributaries (Tarazá and Nechí Rivers) [ 56 ].…”
Section: Discussionsupporting
confidence: 62%
“…muyscorum , and P . magdalenae spawn downstream from the Porce III dam, especially during operation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations